Psychiatrie, genre et sexualités dans la seconde moitié du XXe siècle - Arena, Francesca; Chiletti, Silvia; Coffin, Jean-Christophe (Comment s'en sortir?, 2015)
Les diagnostics cliniques et les différentes nosographies psychiatriques qui ont été établies dans la deuxième moitié du XXe siècle, notamment dans les différentes éditions du manuel américain de diagnostic et statistique des troubles mentaux (DSM), montrent qu'un nombre très significatif de troubles sont envisagés comme étant genrés. Plusieurs controverses ont marqué l'histoire de ces diagnostics depuis les années 1950 : d'abord celui des sexualités et de leurs frontières floues, ensuite la notion controversée d'identité de genre, enfin la problématique des troubles périnataux. Si le principe de différentiation constitue un élément incontournable de la pensée psychiatrique, le façonnage et l'usage du concept de « genre » révèlent des tensions entre la psychiatrie et la société (notamment les mouvements gay, féministes et trans) mais aussi au sein de la psychiatrie elle-même. Il apparaît évidant que, dans les classifications psychiatriques, les normes sociales de genre sont intégrées de manière passive et acritique, au point que l'usage du concept de genre peut amener à l'inverse à renforcer la naturalisation des comportements alors même que, dans les sciences sociales, il est utilisée pour interroger et déconstruire la prétendue naturalité de la différence des sexes.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques; violences; états-unis

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (Collection Logiques sociales. Série Sociologie du genre, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle